Hydrothermal Synthesis and Crystal Structure of bis-(1,10-Phenanthroline)cobalt(II) Thiophene-2,3-dicarboxylate - Zhu, M.; Wang, X.N. (Asian Journal of Chemistry, 2015)
One new cobalt compound with Co(NO3)2·6H2O, thiophene-2,3-dicarboxylic acid and 1,10-phenanthroline (1,10-phen) has been successfully synthesized. Compound shows a one-dimensional framework. The 3D supramolecular structure is formed via hydrogen bonding connection.